Tumor P-Glycoprotein Correlates with Efficacy of PF-3758309 in in vitro and in vivo Models of Colorectal Cancer - Bradshaw-Pierce, Erica L.; Pitts, Todd M.; Tan, Aik-Choon; McPhillips, Kelly; West, Mark; Gustafson, Daniel L.; Halsey, Charles; Nguyen, Leslie; Lee, Nathan V.; Kan, Julie L.; Murray, Brion W.; Eckhardt, S. Gail (Frontiers in Pharmacology, 2013)
P-glycoprotein (P-gp), a member of the ATP-binding cassette transporter family, is overexpressed in a number of different cancers and some studies show that P-gp overexpression can be correlated to poor prognosis or therapeutic resistance. Here we sought to elucidate if PF-3758309 (PF-309), a novel p-21 activated kinase inhibitor, efficacy was influenced by tumor P-gp. Based on in vitro proliferation data, a panel of colorectal cancer cell lines were ranked as sensitive or resistant and ABCB1 (P-gp) expression was evaluated by microarray for these cell lines. P-gp expression was determined by western blot and activity determined by rhodamine efflux assay. Knock down of P-gp and pharmacologic inhibition of P-gp to restore PF-309 activity was performed in vitro. PF-309 activity was evaluated in vivo in cell line xenograft models and in primary patient derived tumor xenografts (PDTX). Mice were treated with 25 mg/kg PF-309 orally, twice daily. On the last day of treatment, tumor and plasma were collected for PF-309 analysis. Here we show that ABCB1 gene expression correlates with resistance to PF-309 treatment in vitro and the expression and activity of P-gp was verified in a panel of resistant cells. Furthermore, inhibition of P-gp increased the sensitivity of resistant cells, resulting in a 4-100 fold decrease in the IC50s. Eleven cell line xenografts and 12 PDTX models were treated with PF-309. From the cell line xenografts, we found a significant correlation between ABCB1 gene expression profiles and tumor response. We evaluated tumor and plasma concentrations for 8 tumor models (3 cell line xenografts and 5 PDTX models) and a significant correlation was found between tumor concentration and response. Additionally, we show that tumor concentration is approximately 4-fold lower in tumors that express P-gp, verified by western blot. Our in vitro and in vivo data strongly suggests that PF-309 efficacy is influenced by the expression of tumor P-gp.